Doxorubicin Loaded Gold Nanoparticles Mitigate Liver Fibrosis and Inflammatory Cytokines Gene Expression in Rat - Ishaq, Yasmeen; Naeem, Hamna; Khurshid, Sana; Tabbasam, Rabia; Haider, Zeeshan (Recent Advances in Drug Delivery and Formulation, 2022)
Background: Gold nanoparticles have the potential to be used as a carrier in drug delivery systems due to their small size, large surface area and short circulation time in blood. Objective: This study demonstrates that doxorubicin conjugation with gold nanoparticles (AuNPs) may reduce its toxicity as well as improve therapeutic efficacy. Methods: Five groups of Albino rats were used; 1: healthy control, 2: injured, 3: injured and treated with Dox, 4: injured and treated with AuNPs, 5: injured and treated with AuNPs: Dox. At the end of the experiment, blood and liver tissues were processed for biochemical and histopathological analysis. The expression of collagen, HO-1, IL-6 and TNF-α genes involved in liver fibrosis was observed through real-time PCR. Results: At the end of the experiment, it was observed that the body weights of DOX-treated rats decreased by 0.72%, however, AuNPs and Au: DOX-treated rats were 15.3% and 29.13% respectively. The percentage of liver protection determined through alanine aminotransferase and aspartate aminotransferase levels in DOX, AuNPs and AuNPs: DOX treated groups were 39.21%, 79.26%, 98.17% and 47.77%, 84.17%, 97.92%, respectively, representing better recovering liver in Dox-AuNPs treated rats compared to others. Histopathological and gene expression studies further support the findings. The mRNA expression levels of inflammatory and oxidative stress-related genes HO-1, IL-6 and TNF- α were upregulated in the injured group but downregulated in the treated group. Conclusion: As depicted through biochemical, histopathological and gene expression studies, Au: DOX conjugate group seems to be protective against liver fibrosis.
Keywords: Heam oxygenase